2016
DOI: 10.1016/j.redox.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulatory mechanisms of osteoclastogenesis through cytoprotective enzymes

Abstract: It has been reported that reactive oxygen species (ROS), such as hydrogen peroxide and superoxide, take part in osteoclast differentiation as intra-cellular signaling molecules. The current assumed signaling cascade from RANK to ROS production is RANK, TRAF6, Rac1, and then Nox. The target molecules of ROS in RANKL signaling remain unclear; however, several reports support the theory that NF-κB signaling could be the crucial downstream signaling molecule of RANKL-mediated ROS signaling. Furthermore, ROS exert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 94 publications
5
60
0
Order By: Relevance
“…Although a direct binding assay was not performed to confirm the interaction between STIP1 and PrPc in the osteoclast precursor cells, the results from several functional studies were supportive to our conclusion, i.e., 1) a dose-dependent induction of PrPc expression by hrSTIP1; 2) the anti-PrPc antibody impeded the hrSTIP1-induced osteoclast differentiation; and 3) the combination of anti-STIP1 and anti-PrPc antibodies inhibited the CTSK expression significantly. In vivo , several cancer-associated conditions, including hypoxia and oxidative or endoplasmic reticulum stresses can activate PrPc transcription [37, 38], which also been shown to increase osteoclast activity [39, 40]. Thus, the STIP1-PrPc signaling in osteolysis might be augmented and an in vivo verification in the bone metastasis RCC animal model or patient specimens would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct binding assay was not performed to confirm the interaction between STIP1 and PrPc in the osteoclast precursor cells, the results from several functional studies were supportive to our conclusion, i.e., 1) a dose-dependent induction of PrPc expression by hrSTIP1; 2) the anti-PrPc antibody impeded the hrSTIP1-induced osteoclast differentiation; and 3) the combination of anti-STIP1 and anti-PrPc antibodies inhibited the CTSK expression significantly. In vivo , several cancer-associated conditions, including hypoxia and oxidative or endoplasmic reticulum stresses can activate PrPc transcription [37, 38], which also been shown to increase osteoclast activity [39, 40]. Thus, the STIP1-PrPc signaling in osteolysis might be augmented and an in vivo verification in the bone metastasis RCC animal model or patient specimens would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 (Thimmulappa et al, 2002), Sirtuin (Chen et al, 2011), and FOXO (Liu et al, 2005) are major regulatory pathways for cytoprotective enzymes (Kanzaki et al, 2016a). Figure 2 summarizes the linking the periodontitis, the regulatory pathways of ROS scavenging enzymes, and the defense mechanism against tissue destruction.…”
Section: Mechanisms That Protect Against Oxidative Stressmentioning
confidence: 99%
“…Interestingly, ROS produced by osteoclasts play a role in promoting the differentiation of these cells through Akt, NF-κB and ERK activation [37,38], suggesting that ROS function as a cell signaling mediator in osteoclastogenesis. Recent study reported that ROS-induced promotion of osteoclastogenesis is downmodulated by an antioxidant response system involving Nerf2 in the homeostatic context [39,40], indicating the presence of a sophisticated regulatory mechanism for ROS-associated osteoclastogenesis. On the other hand, low level of NO increases the generation of mature osteoclasts by up-regulating actin remodeling in mononuclear preosteoclasts, thereby promoting cell fusion processes required for multi-nucleation of OCm [32].…”
Section: Discussionmentioning
confidence: 99%